Altitude‐resolved shortwave and longwave radiative effects of desert dust in the Mediterranean during the GAMARF campaign: Indications of a net daily cooling in the dust layer. Issue 8 (20th April 2015) - Meloni, D.; Junkermann, W.; di Sarra, A.; Cacciani, M.; De Silvestri, L.; Di Iorio, T.; Estellés, V.; Gómez‐Amo, J. L.; Pace, G.; Sferlazzo, D. M.
Abstract Desert dust interacts with shortwave (SW) and longwave (LW) radiation, influencing the Earth radiation budget and the atmospheric vertical structure. Uncertainties on the dust role are large in the LW spectral range, where few measurements are available and the dust optical properties are not well constrained. The first airborne measurements of LW irradiance vertical profiles over the Mediterranean were carried out during the Ground‐based and Airborne Measurements of Aerosol Radiative Forcing (GAMARF) campaign, which took place in spring 2008 at the island of Lampedusa. The experiment was aimed at estimating the vertical profiles of the SW and LW aerosol direct radiative forcing (ADRF) and heating rates (AHR), taking advantage of vertically resolved measurements of irradiances, meteorological parameters, and aerosol microphysical and optical properties. Two cases, characterized respectively by the presence of a homogeneous dust layer (3 May, with aerosol optical depth, AOD, at 500 nm of 0.59) and by a low aerosol burden (5 May, with AOD of 0.14), are discussed. A radiative transfer model was initialized with the measured vertical profiles and with different aerosol properties, derived from measurements or from the literature. The simulation of the irradiance vertical profiles, in particular, provides the opportunity to constrain model‐derived estimates of the AHR. The measured SW and LW irradiances were reproduced when the model was initialized with the measured aerosol size distributions and refractive indices. For the dust case, the instantaneous (solar zenith angle, SZA, of 55.1°) LW‐to‐SW ADRF ratio was 23% at the surface and 11% at the top of the atmosphere (TOA), with a more significant LW contribution on a daily basis (52% at the surface and 26% at TOA), indicating a relevant reduction of the SW radiative effects. The AHR profiles followed the aerosol extinction profile, with comparable peaks in the SW (0.72 ± 0.11 K d−1) and in the LW (−0.52 ± 0.12 K d−1) for the considered SZA. On a daily basis, the absolute value of the heating rate was larger in the LW than in the SW, producing a net cooling effect at specific levels. These are quite unexpected results, emphasizing the important role of LW radiation.